0144 Subjective, But Not Objective, Measures of Sleep Continuity Are Associated with Perceived Stress in a Community Sample. (27th April 2018) - Doyle, C Y; Ruiz, J M; Taylor, D J; Dietch, J R; Ahn, C; Allison, M; Smith, T W; Uchino, B N; Smyth, J W
Abstract: Introduction: Poor sleep is associated with a range of worse physical health outcomes including cardiovascular disease morbidity and mortality. One potential pathway is through the effects of stress. However, findings on the relationship between perceived stress and sleep are mixed with few studies comparing/contrasting specific subjective vs. objective sleep continuity parameters above and beyond global self-reported sleep quality indices (e.g., single time-point retrospective questionnaires or single questions). This study addresses this gap in the literature in a community cohort with contemporary measurement strategies. Methods: Participants were a community sample of 300 healthy adults (150 men, 150 women) ages 21 to 70 years enrolled in the North Texas Heart Study (PI: Ruiz). The sample was stratified by age within gender and race/ethnicity, and the mean age at enrollment was 42.44 years (SD=12.76). At baseline, participants completed the Perceived Stress Scale (PSS), a 10-item validated scale of the frequency of stressful beliefs in the past month. Actigraphy using AW Spectrum Actiwatches and sleep diary data were collected over a 48-hour period. All dependent variables were averaged over the study period. Actigraphic and sleep-diary measures of sleep continuity included sleep onset latency, wake after sleep onset, terminal wakefulness, sleep efficiency, and actigraphic number of awakenings. Results: Linear regressions were conducted for each sleep parameter. Average PSS score was not significantly associated with objective measures of sleep latency, wake after sleep onset, number of awakenings, and sleep efficiency, all b 's<1.29, all p 's< 0.48. However, among subjective indices, higher average PSS score was significantly associated with longer sleep latency, longer terminal wakefulness, and lower sleep efficiency, all b 's>3.8, all p 's<.04. Conclusion: The current study demonstrates a relationship between perceived stress and subjective but not objective sleep continuity indices. These findings may have bearing on how the associations between sleep and perceived stress can be interpreted. Support (If Any): The North Texas Heart Study was supported by the National Heart, Lung, and Blood Institute.